(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
On the 1st of November 2020, Algerians casted their vote on Tebboune’s constitutional reform. The President sponsored the reform as a step towards «a new Algeria». However, he found a strong and diverse opposition, including both the members of the Hirak and Islamist parties. As a result, despite the prevalence of the “yes”, the extremely low turnout proved that most Algerians did not support the reform and put the President in a thorny position: was it a victory or a defeat? Will he manage to realise his project of a «new Algeria»?